Millán-Astray’s Translation of Nitobe’s Bushido: The Soul of Japan - Beeby, Allison; Rodríguez, María (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2009)
AbstractThe translation of Inazo Nitobe’s Bushido: the Soul of Japan (1905) by Millán-Astray, the founder of the Spanish Foreign Legion (1941), has been studied from the point of view of the contexts, pretexts and texts of the source text (ST) and the translated text (TT). Nitobe’s context and pretext meant that his discourse was primarily one of cultural mediation, an attempt to build bridges between East and West, but also to strengthen the position of Japan. Millán-Astray’s context and pretext meant that his discourse was intended to inspire the youth of Spain, but also, and this was even more important, to strengthen Franco’s regime and give prestige to the Spanish Foreign Legion. The pretexts of both author and translator can be found in the paratextual elements of the ST (1905) and the TT (1941). However, both texts have been re-edited several times in different formats, without the original introductions and prologues and this raises the question of how the inclusion or omission of this information may affect the reader’s interpretation of text as discourse.